The Contribution of some Anthropometric and Physical ‎Measurements in Predicting Performance for Long and Triple ‎Jumps - Rami Halaweh; Waleed Hammouri (My University, 2008)
The purpose of the current study was to investigate the contribution ‎of some anthropometric and physical measurements in predicting ‎performance for long and triple jumps the descriptive approach was used ‎‎.Eighty four students of the faculty of physical Education .the ‎anthropometric and physical measurements represented by heights, ‎circumferences. Explosive power, strength, speed flexibility, and ‎performance for long and triple jumps. Using step wise method was used ‎results revealed that the measurements that contributed to long jump ‎where: leg length (64.7%) ,thigh length(9.6%),calf length(2.0%),forearm ‎and upper arm length(1.7%),body height(1.6%),calf and thigh ‎lengths(1.3%),calf circumference (1.0%),the previous contributions sum ‎was 88.6%,regarding the contribution related to physical measurements ‎‎,It was: stand jump(91.8%),legs strength(1.0%),the total physical ‎measurements was93.0%. Results also revealed that the anthropometric ‎and physical measurements contributing to triple jump were: body height ‎‎(66.1%), thigh length (6.7%), leg length (1.8%),which summed 74.6% ‎concerning the contribution related to physical measurements it was ‎found that: stand jump(86.2%),Grip force(1.2%),legs force (1.2%) which ‎summed 88.6%.the best equations that the study was reached is‎ ‎-‎ Long jump=3.265 ×stand jump +0.004 ×legs force – 4.732 ‎ ‎-‎ Triple jump=5.153× stand jump+ 0.0421× Grip force+0.0771× legs ‎force - 5.792‎ ‎-‎ Triple jump=5.461×body height+0.0599× thigh length+0.0368×leg ‎length-6455.‎ It was recommended to do follow up anthropometric and physical ‎measurements for beginners in both long and triple jumps to evaluate the ‎training state and physical growth, and to construct training programs to ‎develop jump force and the force of legs and arms.

هدفت الدراسة التعرف إلى القياسات الأنثروبومترية والبدنية التي تساهم في التنبؤ في ‏الإنجاز الرقمي للوثب الطويل والوثب الثلاثي، ولتحقيق ذلك أجريت الدراسة على عينة قوامها ‏‏(84) طالبا من طلاب كلية التربية الرياضية في الجامعة الأردنية، واستخدم المنهج الوصفي وتم ‏إجراء مجموعة من القياسات الأنثروبومترية والبدنية المتعلقة بالأطوال والمحيطات والقوة ‏الانفجارية والقوة الثابتة والسرعة والمرونة إضافة إلى المستوى الرقمي والمتمثل في مسافتي ‏الوثب الطويل والوثب الثلاثي واستخدم تحليل الانحدار الخطي المتعدد بالأسلوب المتدرج ‏وأشارت نتائج الدراسة إلى تنبؤ القياسات الأنثروبومترية وعناصر اللياقة البدنية بمسافة الوثب ‏الطويل وهي على النحو التالي: طول الرجل وبلغت نسبة ألمساهمة الجزئية 64.7 طول الفخذ ‏‏9.6 وطول الساق 2.0 وطول الساعد والعضد 1.7 والطول 1.6 وطول الساق والفخذ 1.3 ‏ومحيط سمانة الساق 1.0 وبلغ مجموع نسب التباين المفسر 88.6، اما بالنسبة للتنبؤ في ‏القياسات البدنية فكان الوثب من الثبات حيث بلغت نسبة المساهمه الجزئية 91.8، قوة الرجلين ‏‏1.2 وبلغ مجموع نسب التباين المفسر 93.0، كما أظهرت الدراسة أن القياسات الأنثروبومترية ‏والصفات البدنية التي تساهم في التنبؤ بمسافة الوثب الثلاثي هي الطول حيث بلغت نسبة ‏المساهمة الجزئية 66.1، طول الفخذ 6.7، طول الرجل 1.8 وبلغ مجموع نسب التباين المفسر ‏‏74.6 اما بالنسبة للتنبؤ في القياسات البدنية فكان الوثب من الثبات حيث بلغت نسبة المساهمة ‏الجزئية 86.2 وتمثل أعلى نسبة من نسب التباين المفسر وقوة القبضة 1.2وقوة الرجلين 1.0 ‏وبلغ مجموع نسب التباين المفسر 88.6، ومن افضل المعادلات التي توصلت اليه الدراسة.‏ ‏-‏ الوثب الطويل = 3.265 × الوثب من الثبات + 0.004 × قوة الرجلين – 4.732.‏ ‏-‏ الوثب الثلاثي = 5.153 × الوثب من الثبات + 0.0421 × قوة القبضة + 0.0771 × ‏قوة الرجلين – 5.792.‏ ‏-‏ الوثب الثلاثي = 5.461 × الطول الكلي + 0.0599 × طول الفخذ + 0.0368 × طول ‏الرجل – 6.455 .‏ ويوصي الباحثان بإجراء قياسات أنثروبومترية وبدنية تتبعية للاعبين المبتدئين في فعاليتي ‏الوثب الطويل والثلاثي بغرض تقويم الحالة التدريبية والنمو الجسمي. وبناء البرامج التدريبية ‏التي تعمل على تنمية قوة الوثب وقوة عضلات الرجلين والذراعين. والاهتمام بالقياسات ‏الأنثروبومترية عند انتقاء الناشئين , والقيام بإجراء دراسات مشابهه على الطالبات.‏
مساهمة بعض القياسات الأنثروبومتريه والبدنية للتنبؤ في الإنجاز الرقمي لفعاليتي الوثب ‏الطويل والوثب الثلاثي